IMPLEMENTASI METODE DISKUSI DENGAN PENGGUNAAN WHATSAPP DALAM PEMBELAJARAN IPS DI SDN X SIMPANG GAUNG - Siti Jariah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Social studies (IPS) subjects consist of fairly solid material, and understanding thevmaterial is usually performed by memorizing so that the students become bored. The lack of students' involvement also affects the learning process. Passive students make learning to be ineffective. One of the interesting learning methods for IPS lessons is the discussion method. This method refers to presenting or delivering lesson material in which educators provide opportunities for students or groups of students to hold scientific talks to gather opinions, make conclusions, or draw up various alternative solutions to a problem. This research used Classroom Action Research (CAR), applying a model of Kemmis and Mc. Taggart. This research was conducted at SDN X Simpang Gaung. The subjects of this research were 26 students at grade VI. This research revealed that the students' learning outcomes increased significantly after using the discussion method for two cycles. The average score in Cycle I was 75.25, with a classical completeness value of 54.93%. Meanwhile, the average score in Cycle II was 83.25, with a classical completeness value of 73.26%. This research concluded that the discussion method improved students' abilities and attractiveness to learn IPS subjects through WhatsApp.